The Rahmatal Lil Alamien Islamic Education Paradigm in Various Perspectives - maftuhah, maftuhah; Khozin, Khozin; Nurhakim, Moh. (Jurnal ini diterbitkan oleh: PGSD FKIP Universitas Muhammadiyah Tasikmalaya, 2024)
The Paradigm of Islamic Religious Education (IRE) with the concept of